PROSEDUR PENGUJIAN SUBTANTIF ATAS AKUN UTANG USAHA KLIEN PADA KAP KANAKA PURADIREDJA, SUHARTONO - Nour Syifaa Fauziyyah (2023)
Accounts payable is an obligation of the client company that arises due to purchases or services received on credit. Debt also has good benefits for a company, therefore an audit is needed to minimize recording errors that occur which can be detrimental to client companies. This client company is engaged in manufacturing. In carrying out the audit, the aim is to find out, analyze and understand the audit process, especially when carrying out substantive testing procedures for accounts payable accounts at KAP Kanaka Puradiredja, Suhartono. This writing uses a qualitative descriptive analysis method to state or describe the process of carrying out substantive testing procedures on accounts payable accounts, while collecting data by conducting literature searches, observations, interviews and documentation. The result of this writing is a detailed substantive testing procedure. After substantive testing is carried out, it will produce audit findings related to the fairness of the assertions made related to trade payables. At this client company, the authors can conclude that there was no material misstatement found so that the trade payable balance has been presented fairly and has met the established standards.